Ruled Surfaces in E4 with Constant Ratio of the Gaussian Curvature and Gaussian Torsion - Goncharova, O. A. (Журнал математичної фізики, аналізу, геометрії, 2008)
Local and global existence theorems on the ruled surfaces with a constant ratio of the Gaussian curvature and Gaussian torsion are proved. Mathematics Subject Classification: 53A07.